Implementasi Manajemen Peserta Didik Dalam Meningkatkan Layanan Pembelajaran - Muwafiqus Shobri; Wahyu Rivaldo; Siti Zainab (AKSI: Jurnal Manajemen Pendidikan Islam, 2023)
The problem studied in this study is the implementation of student management in improving student learning services at MTs. Miftahul Huda Kepuhteluk, Tambak District. This study aims to (1) describe the implementation of student management in MTs. Miftahul Huda Kepuhteluk, Tambak District, (2) Describe the efforts made by madrasas to improve student learning services at MTs. Miftahul Huda Kepuhteluk Tambak District, and (3) Describe the supporting factors and inhibiting factors of student management in improving student learning services at MTs. Miftahul Huda Kepuhteluk. This study used qualitative research methods. Data collection techniques using interviews, observation, and documentation. Data analysis using data reduction, data presentation, and conclusion. Checking the validity of the data using source triangulation. The results of this study indicate that: (1) Implementation of student management in MTs. Miftahul Huda Kepuhteluk is carried out through management function activities, namely planning, organizing, actuating, and controlling. (2) Efforts made by schools to improve student learning services, namely teachers have used the lecture method, question and answer method, practice method. (3) The supporting factors are from the point of view of teachers who already have a bachelor's degree, while the inhibiting factors come from students who have low IQ.